Comparison of kidney transplant outcomes in HLA compatible and incompatible transplantation: A national cohort study. Issue 12 (21st September 2022) - Rennie, Trijntje J. W.; Battle, Richard K.; Abel, Angela A.; McConnell, Sylvia; McLaren, Robert; Phelan, Paul J.; Geddes, Colin; Padmanabhan, Neal; Clancy, Marc J.; Little, Ann‐Margaret; Turner, David M.
Abstract: Background: Reports of HLA incompatible (HLAi) kidney transplant outcomes are inconclusive, especially in the context of lower level Donor Specific Antibodies (DSA). Methods: Multi‐centre national cohort study of HLAi kidney transplant recipients matched in 1:2 ratio with HLA compatible (HLAc) kidney transplant recipients. HLAi defined as DSA identified by Luminex. Antibody mediated rejection (AMR) and transplant‐survival were analysed using Kaplan–Meier plots. Propensity score (PS) matching was used to compare recipient and transplant survival between groups. Results: We included 61 HLAi and 122 HLAc recipients; mean age 46 years; 60% female. MFIT0 : 3327 (IQR 1352–6458), 23 (38%) were Flow cytometry crossmatch positive (FC‐XMPOS ). DSAPOS /FC‐XMPOS transplantation carried an increased risk of AMR at 1 year (52%) compared to DSAPOS /FC‐XMNEG (27%) and HLAc (0%). Unadjusted death censored graft loss at 3 years was 13% (HLAi) and 8% (HLAc). Three‐year patient survival was 95% in HLAc, 84% in DSAPOS /FC‐XMNEG and 69% in DSAPOS /FC‐XMPOS recipients; 58% of HLAi deaths were infection‐related. HLA incompatibility was associated with a decreased 3‐year survival in our PS‐matched cohort. Conclusion: In kidney transplantation, DSA and positive FC‐XM carries an increased risk of AMR. Despite inferior transplant and survival outcomes compared to HLAc transplantation, it remains a realistic option for highly sensitized patients facing prolonged waiting times and reduced survival on dialysis. Summary at a glance: Compared to HLA compatible transplantation, HLA incompatible kidney transplantation, especially in the presence of a positive FC‐XM, is associated with an increased risk of rejection, inferior graft function and death. For many highly sensitized recipients a compatible transplant is not on offer and HLA incompatible transplantation can be an appropriate alternative to remaining on dialysis.